A 'Team of Five Million'?: Covid-19 and the 2020 New Zealand General Election - Curtin, Jennifer.; Greaves, Lara.; Vowles, Jack (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2020; Political campaigns

Gendering Leadership and Policy during Covid-19: Jacinda Ardern and the Women's Vote - Curtin, Jennifer.; Woodman, V.K.G.; Greaves, Lara (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2020; Political campaigns

The Disappearing 'Team of Five Million'?: The Road to the 2023 Election - Curtin, Jennifer.; Greaves, Lara.; Vowles, Jack (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections -- New Zealand; New Zealand -- Politics and government -- 1972-; New Zealand Parliament -- Elections, 2020; Political campaigns

The Constitution - Jones, Carwyn (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections -- New Zealand; Māori (New Zealand people) -- Politics and government; New Zealand -- Foreign relations; New Zealand -- Politics and government; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand; Tōrangapū

Te Tiriti o Waitangi - Godfery, Morgan; Hayward, Janine (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections -- New Zealand; Māori (New Zealand people) -- Politics and government; New Zealand -- Foreign relations; New Zealand -- Politics and government; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand; Tōrangapū

Māori Political Histories - Greaves, Lara (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections -- New Zealand; Māori (New Zealand people) -- Politics and government; New Zealand -- Foreign relations; New Zealand -- Politics and government; Political parties -- New Zealand; Proportional representation -- New Zealand; Representative government and representation -- New Zealand; Tōrangapū

Epilogue: Te Tiriti Relationships - A Critical Reflection - Stanton-Turei, Metiria (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Beyond Treaty Principles: The Double Trusteeship of te Tiriti o Waitangi - Kawharu, Merata (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Whakarongo ki te tangi o tō tātou Kaitiaki: The Cry of Our Harbour Custodians - Muru-Lanning, Marama; Lanning, Gerald (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

The Enduring Power of Hope: The Impact of the Treaty Settlement Process in Te Tauihu - Johnston, Kerena (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Mana Whenua in Twenty-first Century Aotearoa New Zealand - Kohu-Morris, Jacobi (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

A Modern-day Muru: The Saga of the Wairarapa Moana and Pouākani Whenua - Stanton-Turei, Metiria (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Ihumātao and te Tiriti: Striving for Just Relationships - Jones, Carwyn; Lee-Morgan, Jenny; Hancock, Frances; Matata-Sipu, Qiane; Newton, Pania; Waa, Moana; Short, Nicola; McCreanor, Tim (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

A Treaty Breach 'Born of Hostility to the Promise Itself': Tamariki, Whānau and te Tiriti - Fitzmaurice-Brown, Luke (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

The Treaty of Waitangi in Policy Development - Pirini, Mihiata (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Propagating the Myth that Māori Ceded Sovereignty - McCreanor, Tim; Came, Heather; Berghan, Grant (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) -- Civil rights.; Māori (New Zealand people) -- Government relations.; Māori (New Zealand people) -- Legal status, laws, etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Resisting the Red Wave? The Māori Party’s return to parliament - Greaves, Lara; Morgan, Ella; Hayward, Janine (A Team of Five Million?: The 2020 ‘Covid-19’ New Zealand General Election, 2024)
Keywords: Māori Party; Māori voters; Voting, Parties, Parliament

Pebbles in Shoes? The Māori Electorates in 2023 - Greaves, Lara (Back on Track? The New Zealand General Election of 2023, 2024)
Keywords: Māori electorates; Voting, Parties, Parliament

Chapter 11: The United Nations Declaration on the Rights of Indigenous Peoples and te Tiriti Relationships - Charters, Claire; Te Aho, Fleur; Whare, Tracey (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Summary: "The third in a series committed to discussions of Te Tiriti o Waitangi/Treaty of Waitangi issues. These essays from leading scholars and researchers take a dynamic approach to understanding Tiriti/Treaty relationships, acknowledging the ever-evolving interplay between the Crown and Māori through time. The book addresses pressing issues like Treaty principles, sovereignty, the UN Declaration on the Rights of Indigenous Peoples, and manawhenua relationships to Te Tiriti and settlements. It emphasises the roles of tikanga and rangatiratanga in fostering genuine progress, and envisions a future guided by these principles in advancing Māori-Crown relationships"--Publisher's website.
Keywords: Kāwanatanga; Mana whakahaere; Māori -- Civil rights; Māori -- Government relations; Māori -- Legal status, laws, etc; Mātāpono; Noho-ā-iwi; Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Chapter 6: Contemporary critical legal accounts of the relationship between international law and domestic law and policy - Charters, Claire; Aho, Fleur Te; Whare, Tracey (Handbook of Indigenous Public Policy, 2024)
This chapter outlines juris-significant, but unorthodox, ways in which international and domestic law, policy and practice influence each other with respect to Indigenous Peoples’ norms. In the authors’ view, such an approach paints a more comprehensive and accurate picture of the legal dialogue that occurs than orthodox and positivistic legal accounts. The approach also illustrates unique and potentially powerful ways that Indigenous Peoples and other non-state actors can better realise Indigenous Peoples’ rights in their territories. The chapter begins by briefly introducing international legal norms relevant to Indigenous Peoples before contrasting formal understandings of the law with new accounts of the influence of legal norms. The final, and primary, section seeks to capture the relationship between international law and domestic state law and policy. It focuses upon international law’s relationship with the courts, legislature and the executive in Aotearoa (New Zealand), although the broader existence of this intersect is signalled.